LncRNA NRON promotes M2 macrophage polarization and alleviates atrial fibrosis through suppressing exosomal miR-23a derived from atrial myocytes - Jianan Li; Qingchun Zhang; Haimiao Jiao (Journal of the Formosan Medical Association, 2021)
Background/purpose: miR-23a is a pro-hypertrophic miRNA that inhibits M2 macrophage polarization. A previous study demonstrated that lncRNA NRON alleviated atrial fibrosis through suppression of M1 macrophages activated by atrial myocytes. This study aimed to determine whether NRON promotes M2 macrophage polarization and alleviates atrial fibrosis through suppressing exosomal miR-23a derived from atrial myocytes. Methods: Mouse atrial myocytes were transfected with the NRON overexpression vector or empty vector, followed by Ang II treatment. Exosomes were isolated from the treated atrial myocytes and then co-cultured with RAW264.7 macrophages. The culture medium from RAW264.7 macrophages treated as described above was added to mouse atrial fibroblasts for incubation. Results: We found that exosomes derived from Ang II-treated atrial myocytes inhibited M2 macrophage polarization by transferring miR-23a. NFATc3 could directly bind to the miR-23a promoter. Overexpression of NRON inhibited the expression of miR-23a by inhibiting NFATc3 nuclear transport in Ang II-treated atrial myocytes, resulting in a decrease in the level of miR-23a in atrial myocyte-derived exosomes. Meanwhile, exosomes derived from NRON-overexpressing atrial myocytes promoted M2 macrophage polarization and inhibited expression of fibrosis markers in atrial fibroblasts. Conclusion: NRON promotes M2 macrophage polarization and alleviates atrial fibrosis through suppressing exosomal miR-23a derived from atrial myocytes.